CSR: A Strategic Publicity - Moharana, Tapas Ranjan (Prabandhan: Indian Journal of Management, 2010)
The concept of corporate social responsibility (CSR) came to the picture when there was a need to generate awareness among the corporate sectors to do something for the society and locality whose resources are being used exhaustively. The relationship between business and society is undeniable. They are inter-dependent. Thus CSR basically highlights that it is important for the companies to realize their responsibilities towards the society. Interestingly, the concept has gained importance in the present scenario as companies found it to be the easiest way to get media attention.